Prevalence of Dyslipidemia and Lipid Goal Attainment in Statin‐Treated Subjects From 3 Data Sources: A Retrospective Analysis - Jones, Peter H.; Nair, Radhika; Thakker, Kamlesh M. (Journal of the American Heart Association, 2012)
Background Evidence‐based randomized clinical trials have shown significant benefit of statin treatment with regard to cardiovascular disease. In anticipation of the National Cholesterol Education Program Adult Treatment Panel IV guidelines, we wanted to assess the current state of lipid goal attainment in the high‐risk secondary prevention population in the United States. The objectives of the study were to estimate the proportion of high‐risk patients treated with statin monotherapy who achieved Adult Treatment Panel III–recommended low‐density lipoprotein cholesterol (LDL‐C) goals (<100 mg/dL; optional <70 mg/dL) as well as non–high‐density lipoprotein cholesterol goals (<130 mg/dL; optional <100 mg/dL). Methods and Results This is a cross‐sectional, retrospective study of 3 data sources: electronic medical records (2003–September 2010), administrative claims data (2003–2010), and National Health and Nutrition Examination Survey data (2007–2008). High‐risk patients (≥18 years of age) were defined as those with a history of coronary heart disease or coronary heart disease risk equivalent who had the latest complete lipid panel measurement and had been treated with statin monotherapy for >90 days at the time of the lipid panel. Cardiovascular disease, coronary heart disease, and coronary heart disease risk equivalents were defined on the basis of availability, specific to each data source. Across the 3 data sources, 20% to 26% of high‐risk patients treated with statin monotherapy for >90 days had LDL‐C <70 mg/dL, and 67% to 77% had LDL‐C <100 mg/dL. The percentages of those attaining both LDL‐C goals and non–high‐density lipoprotein cholesterol goals were quantitatively smaller (13.5% to 19.0% and 46% to 70%). Conclusions Across the 3 data sources, there was consistency in the proportion of high‐risk patients treated with statin monotherapy who were at LDL‐C goal. A significant number of these statin‐treated patients had additional dyslipidemias.